Tumor Necrosis Factor‐α and Interleukin‐6 Concentrations in Cerebrospinal Fluid of Dogs After Seizures. (10th October 2014) - Merbl, Y.; Sommer, A.; Chai, O.; Aroch, I.; Zimmerman, G.; Friedman, A.; Soreq, H.; Shamir, M.H.
<x xml:space="preserve">Abstract</x> Background Idiopathic and acquired epilepsy are common in dogs. Up to 30% of these dogs are refractory to pharmacological treatment. Accumulating experimental evidence indicates that brain immune response and presence of inflammatory mediators decrease the threshold for individual seizures and contribute to epileptogenesis. Hypothesis Dogs with seizures have higher cerebrospinal interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) concentrations compared to dogs with no seizures. Methods A prospective double blinded study; cerebrospinal fluid (CSF) and serum IL‐6, TNF‐α and total protein (TP) concentrations were measured by a blinded investigator for the study group and CSF IL‐6 and TNF‐α levels and TP concentrations were measured in the control group (CG). Animals Dogs presented with seizures that had enough CSF collected to allow analysis were included in the study group. Twelve apparently healthy, quarantined, stray dogs served as control (CG). Results Cerebrospinal fluid TNF‐α and IL‐6 concentrations were significantly higher (P = .011, P = .039) in dogs with seizures (0 ± 70.66, 0.65 ± 10.93 pg/mL) compared to the CG (0 ± 19, 0.73 ± 0.55 pg/mL). When assessing cytokine concentrations of specifically the idiopathic epilepsy (IE) dogs compared to the CG, only TNF‐α concentrations (8.66 ± 62, 0 ± 19 pg/mL) were significantly higher (P = .01). CSF TP concentrations were not significantly higher in the study dogs compared to the CG. Conclusions and Clinical Importance Higher TNF‐α and IL‐6 concentration in the CSF of dogs with naturally occurring seizures. The higher supports the hypothesis that inflammatory processes through certain mediators play a role in the pathogenesis of seizures in dogs.